ANALYSIS OF THE DETERMINANTS OF TIMELINESS OF SUBMITTING FINANCIAL REPORTS FOR PROPERTY REAL ESTATE COMPANIES - Sagita, Putri Dewi; Andhaniwati, Erry (Yayasan Education and Social Center, 2024)
Financial reports must be submitted on time by companies listed on the stock market because the information is essential for making investment choices. Many business actors still violate regulations governing the submission of financial reports to the Indonesian Stock Exchange. Thus, this research aims to re-evaluate various factors to identify components that influence how quickly financial reports are submitted. This research used a purposive sampling technique to collect data, and the final data collection was 159 data held by 53 companies that met the criteria. Research data was analyzed using WarpPLS 7.0 software. The research results show that public ownership, leverage, and company size influence the speed of submitting financial reports to property and real estate companies listed on the Indonesia Stock Exchange; profitability does not affect this timeliness